A controlled trial of itraconazole as primary prophylaxis for systemic fungal infections in patients with advanced human immunodeficiency virus infection in Thailand - Chariyalertsak S. (2014)
Cryptococcal meningitis and Penicillium marneffei infection are common serious fungal infections in patients infected with human immunodeficiency virus (HIV) in Southeast Asia. In a prospective, double-blind trial, 63 patients with HIV infection and CD4+ lymphocyte counts of <200 cells/microL were randomized to receive oral itraconazole (200 mg per day), and 66 similar patients received a matched placebo. Both groups were monitored for evidence of invasive fungal infections. Baseline characteristics and the CD4+ cell counts of the 2 groups were similar. In the intent-to-treat analysis, a systemic fungal infection developed in 1 patient (1.6%) assigned to receive itraconazole (P. marneffei) and in 11 patients (16.7%) given placebo (7 patients had cryptococcal meningitis, and 4 patients had P. marneffei infection; P=.003, by the log-rank test). The incidence of recurrent or refractory mucosal candidiasis was significantly reduced in the itraconazole group. The 2 groups did not differ with regard to adverse effects. Primary prophylaxis with oral itraconazole is well tolerated and prevents cryptococcosis and penicilliosis marneffei in patients with advanced HIV infection, especially those with CD4+ lymphocyte counts of <100 cells/microL. However, prophylaxis with itraconazole was not found to be associated with a survival advantage when it was given to patients with advanced HIV disease.